Inclusive Human Development in Pre‐crisis Times of Globalization‐driven Debts. (17th December 2015) - Asongu, Simplice; Efobi, Uchenna; Beecroft, Ibukun
Abstract: The paper verifies the Azzimonti et al . (2014 ) conclusions on a sample of 53 African countries for the period 1996–2008. Authors of the underlying study have established theoretical underpinnings for a negative nexus between rising public debt and inequality in OECD nations. We assess the effects of four debt dynamics on Inequality Adjusted Human Development. Instrumental variable and interactive regressions were employed as empirical strategies. Two main findings were established which depend on whether debt is endogenous to or interactive with globalization. First, when external debt is endogenous to globalization, the effect on inclusive human development is negative, whereas when it is interactive with globalization, the effect is positive. This may reflect the false economics of preconditions. The magnitudes of negative estimates from endogenous related effects were higher than the positive marginal interactive effects. Policy implications were discussed in light of the post‐2015 development agenda.